STRATEGI DAKWAH RIFĀ'IYAH DALAM MENGEMBANGKAN ORGANISASI UMRI (UMMAHATUR RIFA’IYAH) DI ERA GLOBALISASI DESA WONOBOYO, KECAMATAN WONOBOYO, KABUPATEN TEMANGGUNG - Mirna Silfianingsih; Siti Rabiah Adawiyyah; Muhammad Yusuf (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the Rifā'iyyah da'wah strategy in developing the Ummahatul Muslimat Rifā'iyyah Indonesia (UMRI) organization in the era of globalization in Wonoboyo Village, Wonoboyo District, Temanggung Regency. This research employed a qualitative approach with a field research design to obtain an in-depth understanding of the implementation of da'wah strategies and organizational dynamics within the community. Data were collected through observation, interviews, and documentation, and were analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that UMRI plays a significant role as a women's Islamic da'wah organization in preserving, developing, and sustaining the teachings of Rifā'iyyah. Its da'wah strategy is implemented through various regular religious activities, including monthly Islamic study gatherings (pengajian), istighosah (collective supplication), the study of the Tarajumah Book written by Shaykh Ahmad Rifa'i, Qur'anic recitation, and moral and religious guidance. These activities reflect the implementation of the strategies of tilāwah, ta'līm, and tazkiyah, which complement one another in enhancing Islamic understanding, strengthening faith, and fostering the religious character of UMRI members. Amid the challenges of globalization, such as rapid technological development, changing social perspectives, the increasing participation of women in public life, and declining involvement of some members, UMRI has successfully maintained its existence by strengthening religious programs, improving organizational coordination, and utilizing communication media as a means of disseminating da'wah information. This study concludes that the Rifā'iyyah da'wah strategy implemented by UMRI has been effective in supporting organizational development and promoting women's religious empowerment. This effectiveness is reflected in the sustainability of da'wah programs, the improvement of members' understanding of Islamic teachings, and the preservation of Rifā'iyyah religious traditions despite ongoing social changes. Therefore, enhancing human resource quality, developing innovative da'wah methods, and optimizing the use of digital media are essential strategies for strengthening UMRI's existence and expanding the reach of its da'wah activities in the future.